2017
DOI: 10.1186/s12899-017-0028-5
|View full text |Cite
|
Sign up to set email alerts
|

Variation in branchial expression among insulin-like growth-factor binding proteins (igfbps) during Atlantic salmon smoltification and seawater exposure

Abstract: BackgroundIn preparation for migration from freshwater to marine habitats, Atlantic salmon (Salmo salar L.) undergo smoltification, a transformation that includes the acquisition of hyposmoregulatory capacity. The growth hormone (Gh)/insulin-like growth-factor (Igf) axis promotes the development of branchial ionoregulatory functions that underlie ion secretion. Igfs interact with a suite of Igf binding proteins (Igfbps) that modulate hormone activity. In Atlantic salmon smolts, igfbp4,−5a,−5b1,−5b2,−6b1 and−6b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…Activity of the endocrine IGF-I at the gills in turn may be regulated by local IGFBPs. A recent work by Breves et al (2017) reported changes in local igfbp-6bs in the gills and suggested their importance in the development of hypoosmoregulatory ability.…”
Section: Developmental/seasonal Effects (Smoltification)mentioning
confidence: 97%
“…Activity of the endocrine IGF-I at the gills in turn may be regulated by local IGFBPs. A recent work by Breves et al (2017) reported changes in local igfbp-6bs in the gills and suggested their importance in the development of hypoosmoregulatory ability.…”
Section: Developmental/seasonal Effects (Smoltification)mentioning
confidence: 97%
“…There is also emerging evidence that igfbp-5 genes play a role in ionic homeostasis and Igf regulation in zebrafish ( 121 ), stickleback [e.g., Ref. ( 122 )] and Atlantic salmon gills ( 123 ) with Igfbp-5a acting to regulate calcium influx in zebrafish gills ( 121 ) and being differentially expressed and under divergent selective pressures in marine vs. freshwater sticklebacks ( 122 , 124 ).…”
Section: Physiological Roles Of Teleost Igfbpsmentioning
confidence: 99%
“…In adult Atlantic salmon, neither igfbp-6a1 nor - 6a2 were notably expressed across a panel of 11 tissues, while igfbp-6b1 and 6b2 were each broadly expressed, with the latter being especially highly expressed in gill, brain, and spleen ( 16 ). Both igfbp-6b1 and 6b2 were also reported as being highly expressed in Atlantic salmon gills, where they were dynamically regulated during smoltification ( 123 ).…”
Section: Physiological Roles Of Teleost Igfbpsmentioning
confidence: 99%
“…The architecture of IGFBPs consists of three domains: N-terminal and C-terminal domains, which both contribute to its high-affinity IGF binding, and the variable central linker domain that is believed to be important for maintaining structural integrity [ 14 ]. Although different forms of IGFBPs share considerable sequence similarities, each IGFBP type possesses distinct properties and performs stimulatory or inhibitory functions in different IGF-mediated biological mechanisms [ 15 , 16 ]. The differences in their functions are influenced by post-transcriptional modification such as N-linked glycosylation, phosphorylation for protein kinase A or C, proteolysis, and cell surface associations [ 17 ].…”
Section: Introductionmentioning
confidence: 99%